A boundary integral equation over the thin rotating blade of a wind turbine. (October 2016) - Mescheryakov, K.; Sumbatyan, M.A.; Bondarchuk, A.A.
Abstract: In the present paper we study the aerodynamics of a thin rotating Wind Turbine (WT) blade. Under the assumption of high specific speed (i.e. large angular velocity), by using the classical potential theory, the problem is reduced to a dual integral equation over the surface of the blade. Since a certain value of the axial component of the velocity vector, which is not known a priori, is present in the right-hand side of the basic dual integral equation, the method proposed is based on an iteration scheme. This rapidly converges in two-three steps. The method is tested on example of a small WT, by a comparison with the results obtained by the ANSYS-CFX finite-volume software.